Academic Senate Minutes 2015-02-26 - Academic Senate:::::::::
Chair Report. Agenda – approved. Minutes of 2/12/15 approved. Consent item: Revision of the Special Education concentration in the Education MA – Approved. Vice Chair Report. Vice President of Administration and Finance Report. Report from M. Barnard. Electronic Theses proposal – First Reading completed. Special Report: Wiley Journals in the Library – K. Schneider. Vice President of Associated Students Report. Revision to the Academic Council on International Program appointment procedures approved. Request to hold election without requisite number of candidates - approved. Statewide Senators Report. EPC Report. SAC Report. Request for a Posthumous Degree for Dominic Dei Rossi – approved. FSAC Report. CFA Report. Good of the Order.